Calculation of Basic Indicators of Running Safety on the Example of a Freight Wagon with the y25 Bogie - Dizo, Jan; Blatnicky, Miroslav; Molnar, Denis; Falendysh, Anatoliy (Communications - Scientific Letters of the University of Zilina, 2022)
Freight wagons are among the most widely used means of transporting goods by land. Such a number of wagons and transported material and amount of material need to meet requirements in terms of safety and reliability. A wagon bogie is a key element in the wagon running safety point of view. The Y25 bogie is a most used bogie for freight wagons in the region of the central and west Europe. As this bogie was developed several decades ago, it is interesting to evaluate its running properties according to current standards. The presented research brings results of calculation of chosen basic indicators in terms of running safety. The calculations of the freight wagon with the Y25 bogie was performed by means of a multibody model. Simulation computations were carried out for an empty and loaded wagon, which has been running in curves with various radii and at several running speeds.
Keywords: Y25 bogie; freight wagon; running safety; multibody model